Towards integrating the WEF nexus into food systems thinking: A case study of the Philippi Horticultural Area - Bayat, Amiena; Volmink, Mark (New Agenda: SA Journal of Social and Economic Policy, 2024)
In a case study of the peri-urban Philippi Horticultural Area (PHA) outside Cape Town, South Africa, AMIENA BAYAT and MARK VOLMINK uncover the many issues and racial legacies that negatively impact the security and equitable distribution of water, land and energy resources and suggest how the embryonic water, energy and food or WEF nexus applications, already prevalent in the PHA, could strengthen food production and security.